E ‑learning in Higher Education - Dorota Górska (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
The vast use of the Internet and the increasingly widespread access to the latest technologies have become the main reason for the development of remote teaching services. In an effort to modernize the educational offer, higher education institutions placed, in their programs of studies, different possibilities of teaching using „distance learning”. This trend is already very common in the world’s largest universities. The Polish higher education system, keeping the pace with current trends, has created a legal foundation for the use of modern forms of teaching. The current approach to teaching is also a response to the offer of leading universities of the world and thus the search for competitive advantage in the international educational market. The aim of the article is to present main objectives of the teaching method of e ‑learning, and at the same time, to present the legal status and the rules for the use of e ‑learning in Polish higher education. The article is based on the experience of such teaching introduced at the Pontifical University of John Paul II in Krakow.